APPLICATION MODEL NUMBERED HEADS TOGETHER (NHT) TO INCREASE ACTIVENES AND RESULT OF LEARNING IN STUDY OF GEOGRAPHY ON THE BASIS OF COMPETENCIES IDENTIFY THE TYPES OF NATURAL SOURCES CLASS XI CHRISTIAN HIGH SCHOOL KALAM KUDUS SUKOHARJO 2011/2012 - Perdana, Hananto Timor (Pendidikan Geografi, 2013)
Hananto Timor Perdana, 2013. APPLICATION MODEL NUMBERED HEADS TOGETHER (NHT) TO INCREASE ACTIVENES AND RESULT OF LEARNING IN STUDY OF GEOGRAPHY ON THE BASIS OF COMPETENCIES IDENTIFY THE TYPES OF NATURAL SOURCES CLASS XI CHRISTIAN HIGH SCHOOL KALAM KUDUS SUKOHARJO IN THE SCHOOL YEAR OF 2011/2012.This research aim to to know the activeness and result of learning in study of Geography class XI Christian High School Kalam Kudus Sukoharjo in the school year of 2011/2012 with the model study cooperative Numbered Heads Together (NHT). The scope of the material on the basis of competencies identify the types of natural resources. Pursuant to result of research cycle the average activity of the students were still positive at 82.66% while the average amount of student learning outcomes in learning Geography 69.92 (76%). In Cycle II activity of students in the learning process has increased, marked by the average activity of the students were positive at 90.66% with the learning outcomes of students in learning geography also increased to 76.64 (88%). Complete to so that learn the student individually and also clasikal have been fufilled. As for complete boundary by clasikal 85% from amount of student getting value 67 up. From inferential research result that application model study cooperative Numbered Heads Together (NHT) can improve the activeness and result learning student in study of Geography.